Stability control of yeast glucomannans - Zabolockaya Tatyana; Panyavina Karina; Shtaufen Alexandra (BIO Web of Conferences)
The paper presents the results of a stability study of the yeast cell wall glucomannan complex obtained from biomass by cryodesintegration and hydrolysis. Experimental studies have shown reliable results of changes occurring during storage of the test preparation using the accelerated aging method and in the “real time” mode. The results of determining the dynamics of stability indicators for changes in the antagonistic effect of the glucomannan complex during storage based on the standard method (storage of the preparation under recommended conditions) and using an additional technique (storage at elevated temperatures) are analyzed. It has been established that during storage the glucomannan complex loses activity against pathogenic microorganisms and this indicator directly depends on the main external factors. The analysis of the obtained data revealed the identity of the changes that occurred in the preparation, recorded in the samples of the glucomannan complex studied using the accelerated aging method and the “real time” control method.